Gambaran Akhlak Santri Hafizh Quran di Baitul Quran Markaz Al-Ma’tuq - Yahya Muhammad (UMSU, 2022)
This study aims to determine the morals of students who memorize the Quran at Baitul Quran Markaz Al-Ma'tuq. This study uses a qualitative method with a descriptive approach involving as many as five informants. The results of this study indicate that the morals of the students who memorize the Quran at Markaz Ma'tuq can be seen from various aspects of the assessment. 1) Morals to Allah SWT. This can be seen from the daily activities of students in terms of worshiping Allah, always trying to get closer to Allah by multiplying the deeds of worship while in the cottage, including: praying in congregation in the mosque, studying syar'i sciences, muroja'ah Al-Quran. 'an, and other sunnah worship. 2) The character of the students to the teacher can be seen from their polite behavior to the teacher, not criticizing, obedient and obedient to what is ordered by the teachers. 3) Morals to friends. The students care for and care for each other's friends, share, advise and protect each other. 4) Morals of students to parents and society, devoted to both parents and mingling with the community, respecting elders and being polite. The supporting factors for the formation of students' morals are having self-awareness to try to be better, being in a good family and friendship environment.